2013
DOI: 10.1093/trstmh/trt080
|View full text |Cite
|
Sign up to set email alerts
|

Serological investigation of rabies virus neutralizing antibodies in bats captured in the eastern Brazilian Amazon

Abstract: The serological proportion reported in this paper in a large numbers of individuals indicates that the rabies virus circulates quite actively in the study region, but, because of the production of antibodies, the expression of the disease in these individuals is low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 20 publications
2
19
3
1
Order By: Relevance
“…No significant differences were recorded between sex and age of bats in accordance with Thoisy et al 9 , Almeida et al 11 , and Costa et al 12 . However, Oliveira et al 13 found significantly higher proportions of males and adults that were seropositive for rabies.…”
Section: /6supporting
confidence: 83%
See 4 more Smart Citations
“…No significant differences were recorded between sex and age of bats in accordance with Thoisy et al 9 , Almeida et al 11 , and Costa et al 12 . However, Oliveira et al 13 found significantly higher proportions of males and adults that were seropositive for rabies.…”
Section: /6supporting
confidence: 83%
“…rotundus is the main bat species that carries and transmits the rabies virus in Brazil. Expressive prevalence of rabies antibodies has been observed in this species 10,11,12,15 . In this study, although intensive surveys were conducted in locations normally used by this species as shelters, only 11 specimens were collected over 6 years, all in a forest area with mist nets.…”
Section: /6mentioning
confidence: 85%
See 3 more Smart Citations